Predictors of cerclage failure in singleton pregnancies with a history of preterm birth and a sonographic short cervix. Issue 2 (28th March 2021) - Pan, Mian; Fang, Jiao‐Ning; Wang, Xiao‐Xiao; Zhang, Jun; Lin, Zhi
Abstract: Objective: To identify predictors of ultrasound‐indicated cerclage failure in singleton pregnancies for preventing extremely preterm birth. Methods: A retrospective cohort study included 96 singleton pregnancies with ultrasound‐indicated McDonald cerclage in women with previous preterm birth (PTB) and cervical shortening. Descriptive statistics were calculated at baseline and logistic regression analyses were performed to identify the factors associated with cerclage failure. Results: In all, 28 (29%) of the women had a preterm delivery at before 28 weeks. Multivariate analysis identified cervical dilatation, non‐cephalic presentation, and platelet‐lymphocyte ratio (PLR) as independent predictors of cerclage failure (odds ratio [OR] 3.12, 95% CI [confidence interval] 1.01–9.66; OR 5.81, 95% CI 1.04–32.53; OR 1.02, 95% CI 1.01–1.03, respectively). The efficacy of these predictors was evaluated using a receiver operating characteristics curve. The area under the curve was 0.87 (95% CI 0.78–0.96, P < 0.001) with a sensitivity of 78.6% and specificity of 88.2%. Conclusion: Our findings indicated that cervical dilatation, fetal presentation, and PLR were valuable predictors of cerclage failure in singleton pregnancies with a history of PTB and a sonographic short cervix. The results can be potentially used to assess the prognosis of patients after cerclage and alert clinicians to consider enhanced surveillance and administration of individuals at an increased risk. Abstract : Cervical dilatation, fetal presentation, and platelet‐lymphocyte ratio were valuable predictors of ultrasound‐indicated cerclage failure in singleton pregnancies.